Teachers' Voices: Pandemic Lessons for the Future of Education - Lesley Eblie Trudel; Laura Sokal; Jeff Babb (University of Windsor, 2021)
In late 2019 and early 2020, governments around the world closed educational institutions due to the COVID-19 pandemic. A similar response occurred in Canada and resulted in a sudden pivot by teachers from classroom-based instruction to remote teaching. During and shortly after this time, we undertook a survey study of over 2000 Canadian teachers, as well as follow-up interviews with a representative sub-set of those who took part in the initial round of the survey, to gain perspectives on teaching during the pandemic crisis. We summarize the foundations of the entire study and focus on the analysis and discussion of interview data to provide enhanced understanding of initial survey results. This study presents five lessons from the voices of teachers in the initial stages of COVID-19 in Canadian K-12 schools. Each lesson addresses a reality of teaching that was magnified by the pandemic and is highlighted for future consideration of educators in times of uncertainty and change.